Why so many women still take their husband’s last name - Duncan, Simon (The Conversation, 2020)
While some women may be actively involved in choosing their marital name, taking the man’s name remains the norm.
Keywords: 2000 à aujourd'hui; 2010-2019; angleterre; approches et analyses; cours; discipline; droit des femmes*; famille; histoire et politique; mariage; norvège; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexisme; soc2264; sociologie; systèmes d'oppressions; thématiques

Représentations et récits pluriels au sein des familles homoparentales: Reconnaître la diversité familiale pour mieux contrer l’hétéronormativité - Côté, Isabel; Lavoie, Kévin (Service social, 2020)
Cet article propose une mise en récit du parcours de deux chercheur·e·s dont les intérêts de recherche et d’enseignement portent sur les familles issues de la diversité sexuelle. En mettant à l’épreuve le modèle hétéronormatif traditionnel, les familles homoparentales, notamment celles qui ont recours à la procréation assistée, font émerger de nouvelles trames familiales et relationnelles, en plus de rendre visibles les normes culturelles associées à la parenté, à la parentalité et à la concrétisation du désir d’enfant. Dès lors, une compréhension de la diversité familiale en adéquation avec les pratiques sociales contemporaines s’actualise par une prise en compte de la pluralité des expériences vécues par les parents de même sexe et de leurs enfants.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; famille; homoparentalité; hétéronormativité; inégalités; maternité; parentalité; patriarcat; premier cycle; périodes historiques; queer; québec; régions géographiques; sciences humaines; soc2262; sociologie; systèmes d'oppressions; thématiques

Guerrilla Girls: the art of behaving badly - Guerrilla Girls (Group of artists) (Chronicle Books, 2020)
Guerrilla Girls: The Art of Behaving Badly is the first book to catalog the entire career of the Guerrilla Girls from 1985 to present. The Guerrilla girls are a collective of political feminist artists who expose discrimination and corruption in art, film, politics, and pop culture all around the world. This book explores all their provocative street campaigns, unforgettable media appearances, and large-scale exhibitions. Captions by the Guerrilla Girls themselves contextualize the visuals. Explores their well-researched, intersectional takedown of the patriarchy In 1985, a group of masked feminist avengers'known as the Guerrilla Girls'papered downtown Manhattan with posters calling out the Museum of Modern Art for its lack of representation of female artists. They quickly became a global phenomenon, and the fearless activists have produced hundreds of posters, stickers, and billboards ever since. More than a monograph, this book is a call to arms. This career-spanning volume is published to coincide with their 35th anniversary. Perfect for artists, art lovers, feminists, fans of the Guerrilla Girls, students, and activists You'll love this book if you love books like Wall and Piece by Banksy, Why We March: Signs of Protest and Hope by Artisan, and Graffiti Women: Street Art from Five Continents by Nicholas Ganz.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; artivisme; arts; arts visuels et médiatiques; com5170; corps; cours; discipline; histoire de l'art; justice sociale; militance; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; représentation des femme*; régions géographiques; sexisme; sofia; systèmes d'oppressions; thématiques; travail; états-unis

Collectiviser la question parentale: les apports des parenting cultures studies - Martin, Claude (Lien social et Politiques, 2020)
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; care; cours; discipline; europe; france; justice sociale; maternité; parentalité; patriarcat; premier cycle; privilèges; périodes historiques; régions géographiques; sciences humaines; soc2264; sociologie; systèmes d'oppressions; thématiques